Breaking out the box. Beyond deficit thinking in heterogeneous school settings - Paola Dusi (University of Bologna, 2023)
Drawing on authors working from a decolonial standpoint, Southern epistemologies, and prospectivism, the present contribution seeks to set out a theoretical explanation of the academic difficulties faced by students with different cultural background, by re-examining the theoretical underpinning of the deficit thinking. We hypothesise that the coloniality of knowledge provided fertile ground for its development and spread. According to coloniality theory, the domination of culture, subjective experience and knowledge was a key part of the European project of global domination. We argue that rationalist scientific absolutism continues to provide the epistemological foundation of school, education and teacher-training systems with significant repercussions in terms of both the marginal position assigned within the school institution to students presenting multiple forms of diversity, and their chances of academic success. Exploring approaches to knowledges such as the mestizo, transgressive, intercultural decolonial, can help us to find new ways of thinking, living and coexisting without inferiorizing the other. Epistemic decolonization represents a crucial step in the transformation of the school into an educational-didactic space of empowerment and emancipation, even from the deficit view.